Occurrence of naphthalene in honey consumed in turkey as determined by high-pressure liquid chromatography - (:unkn) unknown (INT ASSOC FOOD PROTECTION, 2007)
This study is the first report on an investigation of the naphthalene concentration in samples of contaminated honey consumed in Turkey. Naphthalene was detected using high-performance liquid chromatography with a diode array detector at 220 nm. In one suspected contaminated specimen, the presence of naphthalene was confirmed by gas chromatography with mass spectrometry (GC-MS) at a concentration of 1.13 mu g/kg. The limit of detection was 0.023 mu g/g and the limit of quantification was 0.078 mu g/g with signal-to-noise ratios of 3 and 10, respectively. A total of 100 samples of commercially available honey obtained from markets (53 samples) and street bazaars (47 samples) were analyzed. Mean naphthalene recovery from honey known to be contaminated with 1 mu g/g was 80.4% (SD = 4.84%, n = 7).
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; SOLID-PHASE EXTRACTION; INDUCED OXIDATIVE STRESS; GAS-CHROMATOGRAPHY; ACARICIDE RESIDUES; ELECTRON-CAPTURE; RATS; PESTICIDES; DISPERSION; SAMPLES